Behavioural Intention to Provide Screening and Brief Intervention for Alcohol-Related Injury in the Emergency Department: A Guiding Framework Using The Theory of Planned Behaviour - Flewellen, Rashid W. (Curtin University, 2016)
Alcohol-related injury is a significant public health challenge particularly in Emergency Departments (ED). Staff responses are invariably influenced by a number of factors, that include perceptions of people affected by alcohol, confidence in the ability to respond and demands on limited resources. This thesis aimed to identify attitudes and beliefs associated with responses to alcohol related injury (ARI). The research objective was to answer the following question: “What factors influence an evidence-based response for ED clinicians managing such injuries?” Diverse factors such as low fidelity within intervention implementation, and misconceptions about the role of public health in emergency medicine as well as findings from this study, will contribute to the ability to understand the response.